FRAUD HEPTAGON MODEL TO DETECT FINANCIAL REPORTING FRAUD IN THE INDONESIAN BASIC MATERIALS SECTOR - Siti Nursiah; Mohamad Zulman Hakim; Galuh Putri Maharani; Anindya Ramadhani; Renita Yulian (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
This study aims to analyze the influence of financial targets, financial stability, external pressure, personal financial needs, board turnover, ignorance, greed, effective supervision, industry characteristics, auditor turnover, and the frequency of CEO photo displays on financial reporting fraud in raw material companies listed on the Indonesia Stock Exchange (IDX) in the period 2021–2024. Using purposive sampling, 39 companies were selected, resulting in 156 observations that were analyzed through panel data regression. The results show that financial targets, external pressure, and industry characteristics have a significant effect on financial reporting fraud. Meanwhile, financial stability, personal financial needs, board turnover, ignorance, greed, effective supervision, auditor turnover, and CEO photo frequency do not show a significant effect. These findings indicate that corporate performance pressure and industry characteristics play a major role in influencing the tendency for financial reporting fraud in Indonesia's basic materials sector.